SURVEY OF PREVALENCE AND TYPES OF BACTERIAL CONTAMINATION OF MOBILE PHONES OF PERSONNEL EMPLOYED IN MAJOR WARDS OF EDUCATIONAL HOSPITALS IN YASUJ - R, Chaman1; s, Nargeseyan; R., . Jannesar3; S., . Ravangard2; G., Nikbakht (university of eloued جامعة الوادي, 2018)
The results of this study prevalence of mobile staff of Yasuj hospitals high and according to the everyday use of mobile phones in hospitals and their role in the reproduction and transmission of microbial agents in the role of a public health threat is more pronounced. So, employing different ways to control the growth of bacteria, including restricting the use of mobile phones in hospital and washing hands after using the cell phone is necessary.
artical
Keywords: mobile phone, bacterial infection, hospital staff